Anti-cancer management of head and neck cancers and oral microbiome—what can we clinically obtain? - Makarewicz, Jakub; Kaźmierczak-Siedlecka, Karolina; Sobocki, Bartosz Kamil; Dobrucki, Iwona T.; Kalinowski, Leszek; Stachowska, Ewa (Frontiers in Cellular and Infection Microbiology, 2024)
Head and neck squamous cell carcinoma (HNSCC) exhibits significant genetic heterogeneity and primarily concerns the oral cavity and oropharynx. These cancers occur more frequently in men with a 5-year survival rate below 50%. Major risk factors include human papilloma virus (HPV) (notably type 16), Epstein–Barr virus, tobacco, alcohol, and poor oral hygiene with approximately 4.5% of global cancers linked to HPV. Notably, differences in the microbiome between healthy individuals and patients with head and neck cancers (HNCs) have been identified. Recent studies highlight the significance of certain oral microbes in risk assessment and the potential of the microbiome as a biomarker for HNCs. Additionally, role of the microbiome in metastasis has been acknowledged. Treatment for HNCs includes local methods, such as surgery and radiotherapy, and systemic approaches, such as immunotherapy. Numerous side effects accompany these treatments. Emerging research suggests the beneficial role of preoperative immunonutrition and probiotics in patient outcomes, emphasizing the influence of the microbiome on treatment efficacy. This review explores the reciprocal effects of HNC treatment and the gut microbiome using radiotherapy, brachytherapy, surgery, immunotherapy, and chemotherapy.